MODELING AND IMPLEMENTATION OF A PROPORTIONAL-INTEGRAL CONTROLLER FOR ELECTROVISCOUS DAMPER - OMORODION, I.I; AMIEBENOMO, S.O; B.O.A. Ozigi (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper is a research undertaken on the design, modelling and implementation of a proportional-integral controller. It focuses on how the proportional-integral controller can be applied in controlling the performance characteristics of an electroviscousdamper